PERSEPSI MAHASISWA TERHADAP CALON ANGGOTA LEGISLATIF MANTAN ANGGOTA KORUPSI (STUDI PADA MAHASISWA PPKn FIS UNM) - Musfirah Nurhaerah; Imam Suyitno; Manan Sailan (Jurnal Tomalebbi, 2019)
ABSTRACT, Student Perceptions of Candidates for Legislative Members of Ex-Corruption Prisoners (Study of PPKn FIS UNM Students). This study aims to determine: (1) the knowledge of PPKn FIS UNM students towards prospective legislative members of ex-convicts of corruption; (2) The attitude of PPKn FIS UNM students in selecting legislative candidates for ex-convicts of corruption; and (3) Determinants in students' perceptions of former legislative candidates for corrupt convicts. To achieve these objectives the researchers used a qualitative approach and type of descriptive research. Based on the source, the types of data in this study are qualitative obtained through interviews with students who are active in the Pancasila and Citizenship Education Department, then processed and presented descriptively. The results of the study show that: 1) Students of PPKn FIS UNM know well about candidates for legislative members of ex-convicts of corruption seen from their knowledge of the existence of candidates for legislative members of ex-convicts of corruption originating from online media, regulations relating to elections and candidates, educational background and his political career and ability to evaluate it, 2) The perception of PPKn FIS UNM students towards legislative candidates is divided into two attitudes. First, the attitude of agreeing with the reasons for legality as a human right (HAM) and giving the opportunity for ex-convicts of corruption to improve. Second, disagreeing with reasons of moral accountability and corruption is an extraordinary crime, and 3) There are two determinants in students' perception. First is the source of information, namely the media informant obtaining information about candidates for legislative members of ex-convicts of corruption. Second semester level, namely the informant's lecture period.ABSTRAK, Persepsi Mahasiswa Terhadap Calon Anggota Legislatif Mantan Narapidana Korupsi (Studi pada Mahasiswa PPKn FIS UNM). Penelitian ini bertujuan untuk mengetahui: (1) pengetahuan mahasiswa PPKn FIS UNM terhadap calon anggota legislatif mantan narapidana korupsi; (2) Sikap mahasiswa PPKn FIS UNM dalam memilih calon legislatif mantan narapidana korupsi; dan (3) Faktor-faktor determinan dalam persepsi mahasiswa terhadap calon anggota legislatif mantan narapidana korupsi. Untuk mencapai tujuan tersebut maka peneliti menggunakan pendekatan kualitatif dan jenis penelitian deskriptif. Berdasarkan sumbernya, jenis data dalam penelitian ini ini bersifat kualitatif yang diperoleh melalui metode wawancara terhadap mahasiswa yang aktif di Jurusan Pendidikan Pancasila dan Kewarganegaraan, kemudian diolah dan disajikan secara deskriptif. Hasil penelitian menunjukkan bahwa: 1) Mahasiswa PPKn FIS UNM telah mengetahui dengan baik tentang calon anggota legislatif mantan narapidana korupsi terlihat dari pengetahuannya mengenai keberadaan calon anggota legislatif mantan narapidana korupsi bersumber dari media online, peraturan-peraturan yang menyangkut Pemilu dan Caleg, latar belakang pendidikan dan karir politiknya serta kemampuan untuk mengevaluasinya, 2) Persepsi mahasiswa PPKn FIS UNM terhadap calon anggota legislatif terbagi atas dua sikap. Pertama, sikap setuju dengan alasan legalitas hukum sebagai hak asasi manusia (HAM) dan memberi kesempatan mantan narapidana korupsi untuk memperbaiki diri. Kedua, tidak setuju dengan alasan pertanggungjawaban moral dan korupsi merupakan kejahatan luar biasa, serta 3) Faktor determinan dalam persepsi mahasiswa ada dua. Pertama sumber informasi, yakni media informan memperoleh informasi tentang calon anggota legislatif mantan narapidana korupsi. Kedua jenjang semester, yakni masa perkuliahan informan.